Two Hearts at Risk: Emergency Alcohol Septal Ablation in a Pregnant Woman With Decompensated HOCM - Gi, Weng-Tein (JACC Case Rep, 2020)
Hypertrophic obstructive cardiomyopathy (HOCM) increases the risk for mother and fetus during pregnancy. Alcohol septal ablation (ASA) is an established procedure in nonpregnant patients with HOCM. In this report, we present a case of a 29-year-old woman in her 29th gestational week with decompensated HOCM undergoing a successful ASA. (Level of Difficulty: Advanced.)